2018
DOI: 10.1104/pp.18.00716
|View full text |Cite
|
Sign up to set email alerts
|

Adaption of Roots to Nitrogen Deficiency Revealed by 3D Quantification and Proteomic Analysis

Abstract: Rapeseed (Brassica napus) is an important oil crop worldwide. However, severe inhibition of rapeseed production often occurs in the field due to nitrogen (N) deficiency. The root system is the main organ to acquire N for plant growth, but little is known about the mechanisms underlying rapeseed root adaptions to N deficiency. Here, dynamic changes in root architectural traits of N-deficient rapeseed plants were evaluated by 3D in situ quantification. Root proteome responses to N deficiency were analyzed by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
81
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(87 citation statements)
references
References 71 publications
5
81
1
Order By: Relevance
“…It is well documented that plants can alter root architecture to enhance N acquisition under N deficiency conditions to adapt to N‐deficient environments (Kiba & Krapp, ; Qin et al, ; White et al, ). The hydroponic experiment showed that the root morphologies of the two B. napus genotypes were affected differently: D4‐15 had more root tips and larger root surface area than D2‐1 under N deficient conditions (Figure S1), suggesting that greater plasticity of the root system might contribute to enhanced NupE and NUE in B. napus (Qin et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It is well documented that plants can alter root architecture to enhance N acquisition under N deficiency conditions to adapt to N‐deficient environments (Kiba & Krapp, ; Qin et al, ; White et al, ). The hydroponic experiment showed that the root morphologies of the two B. napus genotypes were affected differently: D4‐15 had more root tips and larger root surface area than D2‐1 under N deficient conditions (Figure S1), suggesting that greater plasticity of the root system might contribute to enhanced NupE and NUE in B. napus (Qin et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…It is well documented that plants can alter root architecture to enhance N acquisition under N deficiency conditions to adapt to N‐deficient environments (Kiba & Krapp, ; Qin et al, ; White et al, ). The hydroponic experiment showed that the root morphologies of the two B. napus genotypes were affected differently: D4‐15 had more root tips and larger root surface area than D2‐1 under N deficient conditions (Figure S1), suggesting that greater plasticity of the root system might contribute to enhanced NupE and NUE in B. napus (Qin et al, ). Besides changes in root architecture, which affects NupE and NutE, such as N assimilation, remobilization of plant N from senescent to newly growing tissues, and alteration of carbohydrate partitioning might also contribute to NUE (Han, Okamoto, Beatty, Rothstein, & Good, ; Tegeder & Masclaux‐Daubresse, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations